2018
DOI: 10.5604/01.3001.0012.5867
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficient solutions for EAF steelmaking

Abstract: Purpose: To review an advanced solutions to improve the energy efficiency of electric arc furnace (EAF), and presentation of own new efficient low-cost solutions with regard to needs of electrometallurgical complex of Ukraine. Design/methodology/approach: Numerical simulation and industrial experiment is used. The patterns and parameters of heat and mass transfer processes, hydromechanics in a steelmaking bath of an arc furnace, thermal operation of water-cooled elements and gas dynamics in EAF workspace, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Hence, as per the analysis [3], which critically analysed the energy efficiency for carrying out various functions in steelmaking, it was observed that most of the supplied energy is required for heating the raw materials, and only a tiny amount of the energy is utilized for melting. Furthermore, electrical energy is preferably used for overheating the charge, while chemical energy is used for heating and melting [28]. From Fig.…”
Section: Factors Affecting Energy Consumption and Subsequent Methods To Optimize Energy Consumptionmentioning
confidence: 99%
“…Hence, as per the analysis [3], which critically analysed the energy efficiency for carrying out various functions in steelmaking, it was observed that most of the supplied energy is required for heating the raw materials, and only a tiny amount of the energy is utilized for melting. Furthermore, electrical energy is preferably used for overheating the charge, while chemical energy is used for heating and melting [28]. From Fig.…”
Section: Factors Affecting Energy Consumption and Subsequent Methods To Optimize Energy Consumptionmentioning
confidence: 99%
“…Timoshenko et al [80][81][82] has reported numerical modeling results using BGI, changing the height/diameter ratio of the EAF. Their results indicate that by increasing the H/D ratio from 0.18 to 0.33, the time to heat the liquid from 1500 to 1650 °C decreases by about 12-16%.…”
Section: Geometry: H/d Ratiomentioning
confidence: 99%
“…where F in is the in ner surface of the workspace, m 2 ) in dynamic lining layer thick ness d = 0.12 m and thermal conductivity l r = 2.9 W/(m ⋅ K) at a temperature difference between working surface and quasi static layer ΔT r = 1200 K, according to [9] 3 10 .…”
Section: Fig 1 Base Eaf Option (I) and Energy-efficient Solutions (Ii)mentioning
confidence: 99%
“…Insufficient energy efficiency of the EAF is associated with the notion of technological efficiency of shallow flat bath with a shape factor (ratio of diameter to depth) m = 5.5-4.5, in con trast with a "deep" bath in converter or ladle furnace unit, hav ing m ≈ 1. Studies [10] have shown the opportunity in reducing of radiation energy loss in the EAF of "large" metallurgy by 8.5-49 % in different conditions due to decrease in m up to 2.5-1.8. The possibilities of steel refining remain no lower than in a furnace with traditional bath geometry, despite re duction of metalslag interface, due to intensification of heat and mass transfer processes under conditions of pneumatic mixing in a "deep" bath.…”
mentioning
confidence: 99%
See 1 more Smart Citation